Reward and commitment toward transformational leadership and teachers’ job satisfaction - Hardianto, Hardianto; Hidayat, Hidayat; Setiawan, Muhammad Nurhisyam Ali (LPMPP Universitas Negeri Yogyakarta, 2025)
This study examines the influence of reward and commitment on transformational leadership and their impact on teacher job satisfaction in the educational sector of Riau Province, Indonesia. The research involved 250 school teachers from various educational levels, selected using purposive sampling based on criteria such as a minimum of two years of teaching experience and active participation in professional development activities. The relationships among reward, commitment, transformational leadership, and job satisfaction were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that both reward and commitment have a direct and significant effect on transformational leadership, which in turn acts as a key mediating variable in enhancing teacher job satisfaction. Bootstrapping analysis confirmed strong statistical significance (p-value = 0.000), supporting all proposed hypotheses. Furthermore, the model demonstrated high construct reliability and validity, with all variables meeting convergent and discriminant validity standards. These findings highlight the importance of implementing effective reward systems and strengthening organizational commitment to foster transformational leadership practices in schools. Such efforts contribute to higher teacher motivation, satisfaction, and professional performance. This study enriches the literature on educational leadership and offers practical insights for school leaders and policymakers to support teacher well-being and improve school outcomes.